Promoting FADH2 Regeneration of Hydroxylation for High-Level Production of Hydroxytyrosol from Glycerol in Escherichia coli - Wang, Huijing; Wang, Lian; Chen, Jianbin; Hu, Minglong; Fang, Fang; Zhou, Jingwen (Journal of agricultural and food chemistry, 2023)
Hydroxytyrosol is a natural polyphenolic compound widely used in the food and drug industries. The current commercial production of hydroxytyrosol relies mainly on plant extracts, which involve long extraction cycles and various raw materials. Microbial fermentation has potential value as an environmentally friendly and low-cost method. Here, a de novo biosynthetic pathway of hydroxytyrosol has been designed and constructed in an Escherichia coli strain with released tyrosine feedback inhibition. By introduction of hpaBC from E. coli and ARO10 and ADH6 from Saccharomyces cerevisiae, the de novo biosynthesis of hydroxytyrosol was achieved. An important finding in cofactor engineering is that the introduction of L-amino acid deaminase (LAAD) promotes not only cofactor regeneration but also metabolic flow redistribution. To further enhance the hydroxylation process, different 4-hydroxyphenylacetate 3-monooxygenase (hpaB) mutants and HpaBC proteins from different sources were screened. Finally, after optimization of the carbon source, pH, and seed medium, the optimum engineered strain produced 9.87 g/L hydroxytyrosol in a 5 L bioreactor. This represents the highest titer reported to date for de novo biosynthesis of hydroxytyrosol in microorganisms.